2022
DOI: 10.1002/ardp.202200472
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing of 5‐nitrofuran‐3,5‐disubstituted isoxazoles: A thriving scaffold to antitrypanosomal agents

Abstract: Chagas disease (CD) is a neglected disease caused by the protozoan Trypanosoma cruzi. The two drugs used in the treatment schedules exhibit adverse effects and severe toxicity. Thus, searching for new antitrypanosomal agents is urgent to provide improved treatments to those affected by this disease. 5-Nitrofuran-isoxazole analogs were synthesized by cycloaddition reactions [3+2] between chloro-oximes and acetylenes in satisfactory yields. We analyzed the structure-activity relationship of the analogs based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Our research group has experience synthesizing small bioactive molecules using different medicinal chemistry approaches, such as bioisosterism and molecular hybridization. Our synthesis strategy is most often inspired by natural products, such as tetrahydrofuran neolignans, whose privileged scaffold offer versatility for diverse biological applications. ,, Grandisin (Figure , compound 5 ), a neolignan obtained from Virola surinamensis, a plant commonly found on the banks of the Amazon River, possesses anti-inflammatory and antioxidant properties. Carvalho and colleagues (2010) demonstrated that grandisin reduced inflammation in formalin-induced and croton-oil-induced paw and ear edema, respectively .…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has experience synthesizing small bioactive molecules using different medicinal chemistry approaches, such as bioisosterism and molecular hybridization. Our synthesis strategy is most often inspired by natural products, such as tetrahydrofuran neolignans, whose privileged scaffold offer versatility for diverse biological applications. ,, Grandisin (Figure , compound 5 ), a neolignan obtained from Virola surinamensis, a plant commonly found on the banks of the Amazon River, possesses anti-inflammatory and antioxidant properties. Carvalho and colleagues (2010) demonstrated that grandisin reduced inflammation in formalin-induced and croton-oil-induced paw and ear edema, respectively .…”
Section: Introductionmentioning
confidence: 99%